2022
DOI: 10.2147/jmdh.s347669
|View full text |Cite
|
Sign up to set email alerts
|

A Global Map of COVID-19 Vaccine Acceptance Rates per Country: An Updated Concise Narrative Review

Abstract: The delay or refusal of vaccination, which defines vaccine hesitancy, is a major challenge to successful control of COVID-19 epidemic. The huge number of publications addressing COVID-19 vaccine hesitancy necessitates periodic review to provide a concise summary of COVID-19 vaccine acceptance rates worldwide. In the current narrative review, data on COVID-19 vaccine acceptance rates were retrieved from surveys in 114 countries/ territories. In East and Southern Africa (n = 9), the highest COVID-19 vaccine acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
151
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(193 citation statements)
references
References 173 publications
(199 reference statements)
9
151
1
1
Order By: Relevance
“…For example, since February 2022, Austria became the first European country to enforce a law making vaccination against COVID-19 compulsory for all citizens over 14 years of age [ 14 ], while several other countries have introduced vaccination mandates for specific population sub-groups, such as healthcare providers [ 15 , 16 , 17 ], public sector employees and employees working in large companies [ 14 , 18 ], school staff, police officers/firefighters/soldiers, and the elderly [ 14 ]. In the Republic of Cyprus, where the current study was conducted, an intense vaccination campaign resulted in 60% of adults being fully vaccinated against COVID-19 (slightly lower than the EU/EEA average) [ 13 ], yet no vaccine mandates had been implemented at the time of publication of the current article, as the general public has strongly opposed such approaches and remains highly skeptical regarding COVID-19 vaccination [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, since February 2022, Austria became the first European country to enforce a law making vaccination against COVID-19 compulsory for all citizens over 14 years of age [ 14 ], while several other countries have introduced vaccination mandates for specific population sub-groups, such as healthcare providers [ 15 , 16 , 17 ], public sector employees and employees working in large companies [ 14 , 18 ], school staff, police officers/firefighters/soldiers, and the elderly [ 14 ]. In the Republic of Cyprus, where the current study was conducted, an intense vaccination campaign resulted in 60% of adults being fully vaccinated against COVID-19 (slightly lower than the EU/EEA average) [ 13 ], yet no vaccine mandates had been implemented at the time of publication of the current article, as the general public has strongly opposed such approaches and remains highly skeptical regarding COVID-19 vaccination [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of economic status, vaccine hesitancy has been noted in mass vaccination campaigns across low-, middle-, and high-income countries ( 17 19 ). Recent studies have shown that COVID-19 vaccine hesitancy is highest among the Middle East and North African countries, Europe and Central Asia, Western and Central Africa ( 20 ). Among African countries, Cameroon, Senegal, and Liberia had the highest vaccine hesitancy due to lower trust in manufacturing companies ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The updated version of the same review found that in East and Southern Africa (n = 9), the highest COVID-19 vaccine acceptance rate was in Ethiopia (92%) and the lowest in Zimbabwe (50%). In West/Central Africa (n = 13), Niger (93%) had the highest rate, and Cameroon (15%) the lowest (2). Among health workers, Israel reported the highest COVID-19 vaccine acceptance rate at 78.1%, while a survey from the Democratic Republic of the Congo indicated a rate of 27.7% (1).…”
Section: Covid-19 Vaccine Uptake and Hesitancymentioning
confidence: 99%